The impact of knowledge management, data culture and the development of data innovation on the quality of the business insights framework - Fatah, Lalu Abdul; Mardiputra, Hamzah M.; Dewanto, Joko (Linguistics and Culture Review, 2022)
This study examines how much the influence of Knowledge Management Process, Information Culture and Information Technology Maturity on the Business Intelligence System Quality. This study uses descriptive analytic research method and SEM-PLS statistic method. Data is collected from questionnaires distributed and returned from the employees of Finance & Accounting Department and Information Technology Department on private higher education at Bandung City, West Java, Indonesia as respondents. The result indicates a positive influence of Knowledge Management Process, Information Culture and Information Technology Maturity partially To the Business Intelligence System Quality.